Efficacy of reduced-intensity or no heparin versus standard heparin anticoagulation in patients on extracorporeal membrane oxygenation: a systematic review and meta-analysis - Zhang, Tianyu; Cheng, Lingling; Cheng, Zhen; Shi, Aili; Shao, Weiying (Frontiers in Medicine, 2026)
ObjectiveThis study aims to evaluate the efficacy of reduced-intensity or no heparin anticoagulation strategy in comparison to standard anticoagulation strategy during extracorporeal membrane oxygenation (ECMO) support.Materials and methodsSystematic literature review and meta-analysis, complying with the PRISMA guidelines (PROSPERO-CRD42025633878).ResultsEleven studies comprising 958 patients were included in the analysis. Four studies included only patients treated with veno-venous extracorporeal membrane oxygenation (V-V ECMO) for acute respiratory distress syndrome or respiratory failure, two studies focused exclusively on patients treated with veno-arterial extracorporeal membrane oxygenation (V-A ECMO), and five studies included a mixture of patients with both modalities. Most studies (n = 8) were of high quality, as indicated by a Newcastle-Ottawa Scale score of ≥ 6. The overall incidence of bleeding complications was 34% (95% confidence interval (CI): 0.35–0.67), without heterogeneity observed among the studies (I2 = 43%). The overall incidence of thrombotic events was 14.6% (95% CI: 0.65–1.54; I2 = 49%). The overall in-hospital mortality was 49% (95% CI: 0.67–1.21; I2 = 41%), while the red blood cell transfusion rate was 41.2% (95% CI: 0.08–1.02; I2 = 76%).ConclusionReduced-intensity or no heparin anticoagulation appears to be a feasible and safe strategy, demonstrating the potential to reduce bleeding complications without a significant increase in thrombotic events, and may be associated with improved patient outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025633878, identifier CRD42025633878.